Construction of Curriculum Development Standards for Vocational Undergraduate Education - Que, Xiaoping; Feng, Liying; Peng, Jinyin (Education Insights, 2026)
Vocational undergraduate education represents a critical evolution in the modern educational landscape, bridging the gap between practical vocational competency and rigorous undergraduate-level academic requirements. As the demand for highly skilled professionals continues to grow globally, there is an urgent need for systematic curriculum standards that effectively balance vocationality with higher education attributes. This study aims to construct a comprehensive curriculum development standard system specifically tailored for vocational undergraduate programs, drawing upon the foundational principles of competency-based education and work-process oriented theories. To achieve this, a multi-faceted methodological approach was employed, encompassing in-depth policy analysis, an extensive literature review, and a systematic comparative study of international vocational education standards. Based on these rigorous investigations, a robust five-dimensional framework is proposed, encompassing curriculum objectives, curriculum content, teaching strategies, the practical teaching system, and curriculum resources. Each dimension is meticulously designed to ensure that students acquire both theoretical knowledge and practical skills relevant to industry demands. The findings of this research provide a highly scientific, adaptable, and operational standard framework for curriculum construction in vocational undergraduate colleges. Ultimately, this proposed system serves as a vital tool to support continuous quality improvement, foster institutional standardization, and enhance the overall efficacy and global competitiveness of vocational undergraduate education.